Metacinema as Diasporic Postmemory in Justin Chon’s Blue Bayou (2021) - Damia Rizka Ghassani; Ari J Adipurwawidjana (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
Blue Bayou (2021), a film by Justin Chon, presents issues of imagination, postmemory, and identity through self-referential techniques. Referring to Marianne Hirsch’s theory on postmemory, this article examines how this film represents imagined moments and how they serve as a postmemory of the history of Korean immigrants, and how this kind of forgetting constitutes the American shared experience. The findings and discussion show that imagined moments in Antonio's subconscious function as postmemory for Antonio, while the film itself serves as a postmemory for America’s imagination. It can be argued that Blue Bayou deliberately acknowledges itself as a film and as fiction to present the world that America imagines and understands. We argue that Blue Bayou conceives memory, fosters imagination, and acts as a documentation for the audience as well as for America’s fragmented memory.